Conception rates in synchronized heifers bred at various times after onset of estrus - R.C. DeBenedetti; G.H. Kiracofe; H.S. Ward; R.M. McKee (Kansas Agricultural Experiment Station Research Reports, 1977)
One hundred seven of 112 heifers were in estrus 1 to 5 days after an injection of prostaglandin F2αgiven when a 7-day synchronization implant was removed. Checks for estrus were made every four hours and heifers were bred 6, 10, 14, 18, 22, or 26 hours after being detected in estrus. Eight heifers were not bred on schedule. Sixty-seven of 99 (67.7%) bred on schedule conceived to first artificial insemination. Conception rates were similar in heifers bred 6 to 26 hours after being detected in estrus, no differences were noted in conception rates between A.M. and P.M. breedings.
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station); 291; Cattlemen& #x27; s Day; 1977; Beef; Conception rates; Synchronization; Estrus